Influence of dietary organic acid, probiotic and antioxidant on the growth performance and nutrient digestibility in growing rabbit (Bangladesh Journal of Animal Science, 2022)
This study was conducted to compare the effects of different feed additives namely, organic acid (citric acid), probiotic (navio plus), and antioxidant (Bio-Sel-E) on the growth performance and nutrient digestibility in growing rabbit to convey a clear message on the use of one specific additive in rabbit diet. Thirty-two crossbred New Zealand White growing rabbit (four to five weeks of age) were randomly assigned to four different groups and reared for a period of fifty six days. Rabbit were fed on green grass (Hymenachne pseudointerrupta) and concentrate mixture (2703 Kcal ME/kg, 16.91 % CP). Additives were added at the top of the concentrate mixture, except for the control group. Compared with the control group, rabbit fed different additives showed 9–13% higher growth rate and 7–11% greater growth velocity; and probiotic supplemented group showed the best result (P